Feature enhancement from electrical resistivity data in an archaeological survey: the Sapelos hillfort experiment (Boticas, Portugal) - Alves, Mafalda Sofia Duarte (2015)
The PoPaTERVA project is developing applied research regarding the comprehension of the multi-layered cultural background of the Terva Valley Archaeological Park, in Boticas, Portugal. One of the main aspects focused on the project is the appliance of remote sensing techniques to enhance non visible archaeological features. An earth resistance tomography (ERT) survey was carried out at the Sapelos hillfort, by the specialized SINERGEO geophysicist’s team, using a Wenner-Schlumberger array. The resulting data was analyzed by the authors in order to extract and verify valid archaeological features regarding the settlement’s structures. There are several adequate systems that can be used to visualize the surveyed data (x, y, z, Ω). However, the authors preferred the open source Visualization Toolkit (VTK) from Kitware Inc., since it supports several visualization and modelling techniques that are useful for interpretation purposes in archaeological contexts: for instance, it is possible to represent the archaeological site as a virtual scale model, which can be freely manipulated. For the Sapelos hillfort, two distinct visualizations were developed to represent the acquired electrical resistivity data. The first one is used to create a comprehensive volume from the surveyed data, which is imported as structured 3D points and mapped into a 3D volume. However, this representation does not provide the necessary insight for analysis purposes, so a second visualization is needed to cluster the relevant data for archaeological research. This visualization is based on contouring algorithms that generate isosurfaces from scalar resistivity values (Ω), therefore enhancing the features with potential archaeological interest.